2014
DOI: 10.1111/1467-9248.12104
|View full text |Cite
|
Sign up to set email alerts
|

Two Levels of Campaigning: An Empirical Test of the Party-Centred Theory of Professionalisation

Abstract: In this article, we address the problem of measuring the professionalism of political campaigns in national parliamentary and European Parliamentary elections by means of a comparative analysis. We use party-level campaign data from two fairly similar EU member states, Germany and Finland, and eight elections between 2004 and 2011. The data are used to build an index of campaign professionalism which significantly improves previous measures by giving more attention to various campaign strategies instead of foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…Professionalisation is often used to describe political parties' use of external experts, for example the political consultants that characterise the US system (see Bowler and Farrell 2000;Farrell et al 2001;Karlsen 2010), as well as parties' increasing use of new (and sometimes old) techniques to communicate with the public, mostly in the context of election campaigns (e.g. Tenscher and Mykkänen 2014). Professionalisation is also perceived as an indicator of centralisation and party leadership empowerment (e.g.…”
Section: Party Professionalisation and Party Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionalisation is often used to describe political parties' use of external experts, for example the political consultants that characterise the US system (see Bowler and Farrell 2000;Farrell et al 2001;Karlsen 2010), as well as parties' increasing use of new (and sometimes old) techniques to communicate with the public, mostly in the context of election campaigns (e.g. Tenscher and Mykkänen 2014). Professionalisation is also perceived as an indicator of centralisation and party leadership empowerment (e.g.…”
Section: Party Professionalisation and Party Professionalsmentioning
confidence: 99%
“…Poguntke and Webb 2005). Consequently, several studies refer to the number of party staff as an indicator of the level of professionalisation and organisational change in political parties (Farrell and Webb 2000;Katz and Mair 1995;Kölln, 2015;Tenscher and Mykkänen 2014). In this article, we delve deeper and focus on the actual role of party employees in political parties.…”
Section: Party Professionalisation and Party Professionalsmentioning
confidence: 99%
“…Tenscher, Mykkänen & Moring, 2012). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Strömbäck, 2009;Gibson & Römmele, 2009;Tenscher et al, 2012;Tenscher, 2013;Tenscher & Mykkänen, 2014 We want to answer this question by differentiating between different means of "new" and direct campaign channels and their perceived importance for election campaigning.…”
Section: Election Campaign Professionalism and The New Mediamentioning
confidence: 99%
“…On the one hand, it has been demonstrated that there are country-and even region-specific patterns of election campaigning in general (Swanson & Mancini, 1996;Plasser, Scheucher & Senft, 1999;Norris, 2000;Farrell, 2002;Plasser & Plasser 2003;Tenscher et al, 2012) and web campaigning in particular (e.g. Kluver, Jankowski, Foot, & Schneider, 2007;Ward et al, 2008;Lilleker, Koc-Michalska, Schweitzer, Jacunski, Jackson & Vedel, 2011;Lilleker & On the other hand, variations in practitioners' understanding of "new" modes of campaign professionalism might be explained by meso factors, namely party's size, ideology, resources and due to facing an internal or external shock (Gibson & Römmele, 2009;Strömbäck, 2009;Tenscher et al, 2012;Tenscher, 2013;Tenscher & Mykkänen, 2014). Against this backdrop, we investigate the following hypotheses:…”
Section: Election Campaign Professionalism and The New Mediamentioning
confidence: 99%
“…La démarche retenue ici s'inscrit donc dans la lignée du travail mené par Paul Webb et Justin Fisher (2003) sur les employés du Parti travailliste britannique et consiste à s'intéresser à la question de la professionnalisation à 11. Appréhendées à partir des éléments suivants : le budget de la campagne, la taille de l'équipe de campagne, la durée de la campagne, son degré de centralisation, la différenciation des outils de communication interne, le nombre d'agences externes recrutées afin d'évaluer le degré d'externalisation, la nature et le degré de feedback (sondage et focus group), le degré de recherche sur les adversaires, la gestion d'événements et de l'information, les différents types de médias mobilisés (gratuits, payants, talk-show), le ciblage des audiences, les types d'outils de diffusion ciblée et le degré de personnalisation de la campagne (Tenscher et Mykkanen, 2014). partir de l'étude du profil (social, politique…) des membres des équipes de campagne numérique des candidats étudiés ainsi qu'à la nature des tâches qui leur étaient confiées, même si ce second aspect n'est que marginalement évoqué dans le présent article.…”
Section: Appréhender La Professionnalisation De La Communication Poliunclassified